In silico screening leads to novel scaffolds with both antifungal and anti-NLRP3 inflammasome activity. Issue 12 (17th December 2021) - Lowes, David; Al-waqfi, Rand; Hevener, Kirk; Peters, Brian
Abstract : Due to structural similarities that exist between established inhibitors of the NLRP3-inflammasome, sulfonylureas Glyburide and MCC-950, and herbicidal-sulfonylureas, that specifically target fungal acetohydroxyacid synthase (AHAS), we sought to determine the potential for compounds to block both inflammation and inhibit fungal growth. In silico screening of ∼250, 000 compounds was used to identify a prioritized list of chemical structures capable of inhibiting both targets. Prioritization of the top 1% of scores identified ∼70 compounds with a diverse set of scaffolds for testing in vitro. Selected hits were used to assess anti-inflammatory function in a THP-1 challenge model with LPS+ATP and resulting IC50 values were obtained. MIC and hyphal-growth assays were conducted to determine potential antifungal activity using media depleted of branched chain amino acids isoleucine and valine, to confirm on target AHAS inhibition. Identification of hits that exhibited low micromolar activity for NLRP3 and AHAS inhibition were selected for SAR study. In vitro testing of the analogs along with molecular docking led to increased knowledge for lead optimization of the potential hits. In silico screening has resulted in IC50 (IL-1β release) and MIC50 (fungal growth) values with low μM potency against several Candida species. In vivo validation will further confirm the potential of the scaffolds for further synthetic-modification for the rationale design of novel dual-purpose drugs